The use of learning support materials in the rural schools of Maputaland, Kwa-Zulu Natal - Van der Merwe, Michelle (Rhodes University, Faculty of Education, Department of Education, 2011)
The African Coelacanth Ecosystem Programme (ACEP) was established in 2002 after the discovery of a colony of coelacanths off the Maputaland coast at Sodwana Bay, KwaZulu Natal. The environmental education and awareness sub-programme developed learning support materials (LSM's) for use in schools and the materials were disseminated annually through teacher education workshops. This study aimed to uncover the use of these LSM's in the rural schools of Maputaland. The active learning framework was used to analyse the materials. Collectively, the ACEP materials cover a range of active learning aspects; however alignment with the curriculum has resulted in an increased focus on experiments, accompanied by a loss of environmental content and a narrowing scope for active environmental learning. Workshop questionnaires and four school case studies revealed the patterns of practice of use of materials in schools. The stated use of materials by teachers is not fully realized in the actual classroom practice which centres on learning content and concept definitions. There is no culture of use of materials in the schools following the annual introduction of ACEP materials. It was also found that the marine and coastal knowledge holding power is outside the realm of the teachers' practice and control. The findings of this study come at a time when there is uncertainty over the future of South African education and the curriculum. This research may inform the environmental education and coastal and marine education field as to their role in education and more specifically the development of learning support materials.
Keywords: Environmental education -- South Africa -- Maputaland; African Coelacanth Ecosystem Programme; Coelacanthiformes -- South Africa -- Maputaland; Teaching -- Aids and devices -- South Africa -- Maputaland; Environmental education -- Curricula -- South Africa -- Maputaland